PROFILE OF HEAD TRAUMA IN FORENSIC DEPARTMENT OF RSUP DR.SARDJITO FROM YEAR 2009 TO 2011. - , GEETHANJALI MAKENTHIRAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Trauma to the head has known to cause disabilities as well as deaths worldwide. Indonesia, being the third most populated country in the world has an increased risk and incidence of occurrence of head trauma. Objective: The objectives of the research are to describe the pattern of occurrence, epidemiology and the statistical profiles of head trauma from year 2009 to 2011 in the Forensic Department of RSUP DR.Sardjito. Method: This is an observational descriptive analytic study, in which the data was collected from medical record. The research population were the deceased who were sent to the Forensic Department of RSUP Dr.Sardjito who had suffered from trauma to the head from year 2009 to 2011. The subject was included if they had any form of trauma to the part of head covered by hair regardless the cause of death was due to the head injury or otherwise. Victims who did not have any injury to the part of head covered by hair or did not have medical record were excluded. Results: The study showed there were 167 cases of deceased that had suffered from trauma to the head that were sent and examined in the Forensic Department of RSUP Dr.Sardjito from year 2009 to 2011. The frequency of head trauma cases was fluctuant by year. There were 111 male victims and 56 female victims. Most victims were between the ages of 21 to 40 years old. The month of October had the highest occurrence of head trauma cases during the 3 years. Fracture of the head is the most common type of injury suffered to the head. Most victims had a single form of head injury. Motor-vehicle accident caused 70% of all cases. Autopsy was only performed on 17% of the head trauma victims. Conclusion: The trend of head trauma is fluctuant by year. There is statistical significant for type of injury in the cause of head trauma and for autopsy performed in the cause of head trauma.